2003
DOI: 10.1245/aso.2003.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of 1-cm Distal Margin After Restorative Rectal Cancer Resection With Sharp Mesorectal Excision and Preoperative Combined-Modality Therapy

Abstract: Our data suggest that for patients with locally advanced rectal cancer undergoing resection and preoperative CMT, distal margins < or = 1 cm do not seem to compromise oncological outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
108
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(118 citation statements)
references
References 19 publications
8
108
0
2
Order By: Relevance
“…Tumor regression has been found to correlate positively with increased survival [11,12,13,14,15,16,17,18,19,20]. Our complete pathologic response rate of 21% following neoadjuvant chemoradiotherapy is comparable to those reported in the recent literature [21,22,23,24].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Tumor regression has been found to correlate positively with increased survival [11,12,13,14,15,16,17,18,19,20]. Our complete pathologic response rate of 21% following neoadjuvant chemoradiotherapy is comparable to those reported in the recent literature [21,22,23,24].…”
Section: Discussionsupporting
confidence: 84%
“…Over the past few years, with increased utilization of preoperative chemotherapy and radiation therapy followed by radical resection, some authors have suggested that distal resection margins of <2 cm may be adequate [14,15,16,17]. The purpose of this study was to review our institutional experience with rectal cancers treated with neo-adjuvant chemoradiation therapy (CRT), followed by radical proctectomy with total mesorectal excision (TME), and analyze the impact of distal resection margin length on outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In the 21st century, better understanding of the distal spread based on the pathological studies justified reduction of the DRM from 20 mm to 10 mm 7, 8. Neoadjuvant CRT enabled the DRM to be decreased to 5–10 mm 9, 10, 11. A DRM of 10 mm is thought to be safe and reasonable for anal preservation when ISR is applied for a very low rectal cancer closer to the anus 12…”
Section: Discussionmentioning
confidence: 99%
“…Also, CRT influenced down‐staging of the tumor, and allowed sphincter‐saving operation for some patients who may have required APR 6. In addition to those aspects, shorter distal resection margin proposed by clinicopathological studies has encouraged surgeons to preserve the anus 7, 8, 9, 10, 11, 12, 13. In 1994, Schiessel et al .…”
Section: Introductionmentioning
confidence: 99%
“…Initially, 5-cm distal margins were considered necessary [14], but data later confirmed that smaller distal margins were not associated with worse oncologic outcomes [15,16]. Margins of less than 1 cm may be acceptable following neoadjuvant chemoradiation therapy in an attempt to preserve the anal sphincter [17,18]. A total mesorectal excision is important and generally provides an adequate circumferential margin (usually greater than 1-2 mm from resected margin to tumor) [19].…”
Section: Rectal Adenocarcinoma Versus Rectal/pelvic Leiomyosarcomamentioning
confidence: 99%